Cardiovascular risk factors as predictors of completed atrioventricular block during hospitalization for Acute Coronary Syndromes. (11th May 2021) - Santos, H; Santos, M; Miranda, H; Almeida, I; Sa, C; Chin, J; Almeida, S; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes Background: The presence of cardiovascular risk factors (CVRF) are directly related to acute coronary syndrome (ACS) occurrence. ACS is a major health problem with multiple complications. Completed atrioventricular block (CAVB) in context of ACS can impact the patient's prognosis, and is not clarified if its presence can be predicted only by CVFR. Objective: Evaluate the impact of the CVRF in CAVB during the hospitalization for ACS. Methods: Multicenter retrospective study, based on the Portuguese Registry of ACS between 1/10/2010-4/09/2019. Patients were divided in two groups: A – without CAVB during the hospitalization for ACS and B – with CAVB during the hospitalization for ACS. CVFR was defined by body mass index, diabetes, arterial hypertension, smoking, coronary artery disease, neoplasia, dyslipidemia, chronic kidney disease and peripheral arterial disease. Logistic regression was performed to assess predictors of CAVB in these patients. Results: 14031 patients were included, 401 in group B (2.9%). Both groups were similar regarding smoking status (p = 0.920), arterial hypertension (p = 0.928), diabetes mellitus (p = 0.249), peripheral arterial disease (p = 0.352) and chronic kidney disease (p = 0.783). Interestingly the group A exhibited higher body mass index (27.4 ± 4.3 vs 26.9 ± 4.5, p < 0.001), dyslipidemia (62.8 vs 53.6%, p < 0.001) and coronary artery disease (20.7 vs 15.0%, p = 0.001). On the other hand, group B presented more females (26.7 vs 31.5%, p = 0.012), mean age (66 ± 13 vs 71 ± 13, p < 0.001) and neoplasia (4.8 vs 7.1%, p = 0.012). Logistic regression revealed that any of the CVRF were a predictor of CAVB during the hospitalization for ACS. Just, age (odds ratio 1.48, p < 0.001, confidence interval 1.16-1.88) has been a predictor of CAVB during hospitalization for ACS. Conclusions: Any CVFR was a predictor of CAVB in context of ACS. Age was a predictor of CAVB during hospitalization for ACS.